2012
DOI: 10.1111/j.1360-0443.2012.04040.x
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal neurobehavior effects following buprenorphine versus methadone exposure

Abstract: Aim To determine the effects of in utero exposure to methadone or buprenorphine on infant neurobehavior. Design Three sites from the Maternal Opioid Treatment: Human Experimental Research (MOTHER) study, a double-blind, double-dummy, randomized clinical trial participated in this sub-study. Setting Medical Centers that provided comprehensive maternal care to opioid-dependent pregnant women in Baltimore, MD, Providence, RI, and Vienna, Austria. Participants 39 full-term infants. Measurements The NICU Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 27 publications
(45 reference statements)
2
43
1
2
Order By: Relevance
“…31 Prior studies analyzing components of the Barker hypothesis have focused on infants developing in more extreme environmental conditions, 27 or from mothers with high-risk pregnancies. 3,32 This study suggests that there is a level of epigenetic variability even among healthy infants and that this may result from more prevalent environmental conditions and stressors that are most likely experienced by the population at large.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…31 Prior studies analyzing components of the Barker hypothesis have focused on infants developing in more extreme environmental conditions, 27 or from mothers with high-risk pregnancies. 3,32 This study suggests that there is a level of epigenetic variability even among healthy infants and that this may result from more prevalent environmental conditions and stressors that are most likely experienced by the population at large.…”
Section: Discussionmentioning
confidence: 85%
“…1 In a short window of time during early prenatal development, neural networks are formed and behavioral pathways are programmed, and this programming is vulnerable to environmental influences. 2 Environmental factors, including maternal stress, mood, and lifestyle, have been linked to altered neurodevelopmental programming and later life behavioral and neurologic outcomes, 3,4 but the molecular mechanisms underlying these relationships remain unclear. 5 The fetal environment is modulated by the placenta, which produces growth factors, neuropeptides and components of monoamine transporter systems, and has been described as a "third brain" linking the mother and infant.…”
Section: Introductionmentioning
confidence: 99%
“…Both buprenorphine and methadone treatment are associated with reduced overdose risk and improved maternal and fetal outcomes in pregnancy (19,44,51,72). Despite strong evidence supporting the use of buprenorphine and methadone, fewer than 1 million Americans are receiving these treatments (87).…”
Section: Tertiary Preventionmentioning
confidence: 99%
“…The American College of Obstetricians and Gynecologists has urged that buprenorphine be considered first-line treatment, but methadone is likely still the gold standard due to slightly higher adherence, more tightly controlled dosing, and insufficient evidence that buprenorphine is superior than methadone treatment (ACOG Committee, 2012). Observation of clinical cohorts has suggested that prenatal buprenorphine may produce fewer neurobehavioral problems (Coyle et al, 2012), higher birthweight, and larger head circumference compared with methadone (Welle-Strand et al, 2013).…”
Section: Buprenorphinementioning
confidence: 99%